The Influence of Salary, Allowances, and Driver Expenses on Total Current Period Profit at PT Bluebird TBK 2016-2023 - Javier, Laurentius Raymond; Soetedjo, Louis Lewinsky; Manurung, Elizabeth Tiur (Universitas Mohammad Husni Thamrin, 2025)
This study aims to analyze the effect of salary, allowance, and driver's expenses on total current period profit at PT Bluebird Tbk during 2016 to 2023. PT Bluebird Tbk is one of the leading transportation companies in Indonesia engaged in the taxi service sector and other land transportation. With long operational experience, this company continues to strive to increase profitability and maintain business sustainability through various financial management strategies. One aspect that plays a role in the company's financial performance is labor costs, which include salaries, allowances, and driver's expenses. This component is an important part of the company's expenditure structure and has the potential to affect the net profit obtained each period. Labor costs are one of the main factors affecting a company's profitability, so understanding its impact is very important for financial management strategies. The analysis was carried out using the regression method on the company's historical data with the help of Microsoft Excel software. The results of the study showed that salary, allowance, and driver's expenses have a significant effect on total current period profit, with a p-value of 0.000000000862996. This finding indicates that the company has positive expectations about the expenditures made for labor. Based on these results, this study recommends that companies manage their workforce load optimally to increase profitability and ensure employee welfare is maintained.